Dipolar Order Parameters in Large Systems With Fast Spinning - Franks, W. Trent; Tatman, Ben P.; Trenouth, Jonah; Lewandowski, Józef R. (Frontiers in Molecular Biosciences, 2021)
Order parameters are a useful tool for quantifying amplitudes of molecular motions. Here we measure dipolar order parameters by recoupling heteronuclear dipole-dipole couplings under fast spinning. We apply symmetry based recoupling methods to samples spinning under magic angle at 60 kHz by employing a variable flip angle compound inversion pulse. We validate the methods by measuring site-specific 15N-1H order parameters of a microcrystalline protein over a small temperature range and the same protein in a large, precipitated complex with antibody. The measurements of the order parameters in the complex are consistent with the observed protein undergoing overall motion within the assembly.